EVALUASI KINERJA PERUSAHAAN PERBANKAN SEBELUM DAN SESUDAH MENJADI PERUSAHAAN PUBLIK DI BURSA EFEK JAKARTA (BEJ) - Payamta, Mas'ud Machfoedz (UGM, 1999)
through an initial public offering (IPO) a firm going public will raise funds or cash which can be to help finance its iperations. An IPO is expected to improve the performance of a firm. Numerous studies examining of IPOs on the jakarta Stock Exchange (JSX) document a positive impact on company performance, but others show inconsistent results. This research investigates whether there is any significant difference in a bank's performance before and after going public. Bank performance is measured using CAMEL rating, which is commpnly used to identify changes in bank performance. In this research bank performance is evaluated based on five aspects: capotal adequacy, asset quality, management, earnings, and liquidity.